THE EFFICACY OF VASAGUDUCHYADI KASHAYAM IN ALCOHOLIC LIVER DISEASE - Patil, Abhijit; Kadam, *Ruta; Kapgate, Sarita; Namewar, Prasad; Pawar, Suryajeet (International Journal of Ayurveda and Pharma Research, 2017)
Alcoholic liver disease (ALD) is a leading cause of morbidity and mortality in India. Chronic consumption of alcohol results in variations in alcohol metabolism, oxidative stress, antigenic adducts formation and acetaldehyde toxicity. These factors cause inflammation, fatty changes, fibrosis of liver cells and raising the transaminases in the blood. There is no specific treatment for ALD.Vasaguduchyadi Kashayam is a classical Ayurvedic formulation stated in Ashtanga Hridayam for the treatment of Jaundice and anemia. The study focuses on the effect of the Vasaguduchyadi Kashayam in ALD for restoration of normal liver function, with the help of investigating 10 subjective and 2 objective parameters. As the Vasaguduchyadi Kashayam is Yakritgami, Kamalanashak and Pandunashak, was used as Trial Drug.Clinical Trials were conducted at Anandvan De-Addiction Centre, Pune. By ballot method 60 well diagnosed male patients of ALD were included in both Control and Trial group each. The diagnosis of ALD was made by documentation of alcohol excess and evidence of liver disease.The control group was allowed to partake symptomatic line of treatment advised by the centre while the trial group was administered Vasaguduchyadi kashayam in a dose of 15ml with luke warm water after meal for the duration of 45 days. Patients of both groups followed complete abstinence from Alcohol and Pathyakar aahar-vihar.The statistical analysis revealed that Trial drug is effective in ALD. It significantly reduces Agnimandya, Aruchi, Hrillas, Trishna and Pitatva besides it significantly normalizes the LFT too.